2018
DOI: 10.1002/jlb.1ru0717-299rr
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and receptors in intestinal B lymphocytes

Abstract: Recent studies indicate that chemoattractant cytokines (chemokines) and their receptors modulate intestinal B lymphocytes in different ways, including regulating their maturity and differentiation in the bone marrow and homing to intestinal target tissues. Here, we review several important chemokine/chemokine receptor axes that guide intestinal B cells, focusing on the homing and migration of IgA antibody-secreting cells (IgA-ASCs) to intestinal-associated lymphoid tissues. We describe the selective regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 143 publications
(232 reference statements)
0
12
0
Order By: Relevance
“…As we summarized before, B cells can act as chemokine producers, which is important to understand the additional functions of B cells apart from their roles via immunoglobulin secretion or antigen presentation. 27 We found that the transcriptional levels of various chemokines in CD11b + B cells were up-regulated during disease, possibly induced by the pro-inflammatory immune environment ( Fig. 4a).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As we summarized before, B cells can act as chemokine producers, which is important to understand the additional functions of B cells apart from their roles via immunoglobulin secretion or antigen presentation. 27 We found that the transcriptional levels of various chemokines in CD11b + B cells were up-regulated during disease, possibly induced by the pro-inflammatory immune environment ( Fig. 4a).…”
Section: Discussionmentioning
confidence: 86%
“…We have previously reviewed the function of activated B cells as chemokine producers . Hence, we next investigated whether CD11b + B cells functioned as chemokine‐producing cells in Treg cell recruitment in PPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally, CCL21 differs from CCL19 because it has a uniquely long C-terminal tail containing an extra 37 amino acids (6 cysteine residues) that are highly positively charged and capable of binding glycosaminoglycans (GAGs) (Nagira et al, 1997; Steen et al, 2014). CCL19 is secreted by mature dendritic cells (mDCs), while CCL21 is secreted from the endothelium of afferent lymphatic vessels (this has been shown in mice, but evidence in humans is lacking), and both are predominantly secreted by the lumen of high endothelial venules, the stromal cells of the draining lymph node and the spleen (Steen et al, 2014; Wang et al, 2018). Due to their differential structures and expression patterns, CCL19 and CCL21 display different binding affinities for specific heparin or heparan sulfate, and distinct signaling responses are required for in vivo functions (Rot and von Andrian, 2004; de Paz et al, 2007; Raju et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CCR7 was the first identified lymphocyte-specific G-protein-coupled receptor (GPCR) with seven transmembrane spanning alpha helices (Birkenbach et al, 1993). CCR7 is expressed on double negative and single positive thymocytes, including naïve T cells, central memory T cells, regulatory T cells, naïve B cells, semi-mature/mature DCs and NK cells, and a minority of tumor cells, and it acts as a key regulator guiding homeostatic lymphocytes to secondary lymphoid organs (Ohl et al, 2004; Comerford et al, 2013; Hauser and Legler, 2016; Wang et al, 2018; Laufer et al, 2019). The CCR7-ligand axis carries out the following three fundamental “cellular reflexes”: message acquisition, semantic extraction and initiation of cell responses (Bardi et al, 2001; Rot and von Andrian, 2004; Griffith et al, 2014).…”
Section: Introductionmentioning
confidence: 99%